Modelling of the pulverized coal plasma preparation for combustion - V. Messerle; A. Ustimenko (Physical Sciences and Technology, 2021)
The main goal of this research is to show the action of pulverized coal in the plasma chamber through computer simulation and numerical experiments carried out with the aid of developed well known thermodynamic, kinetic and multi dimensional computational fluid dynamics based on mathematical models. The data needed for the validation of the numerical procedure were obtained from a cylindrical direct flow burner equipped with a plasmatron (plasma generator) with 100kW of electric power and mounted on a full-scale boiler (Gusinoozersk TPP, Eastern Siberia). The experiments were carried out using ‘Tugnuisk’ bituminous coal. Two mathematical models were employed: the one (‘1D Plasma- Coal’) being one-dimensional, but with an emphasis on complex chemistry, the other (3D FAFNIR) being fully three-dimensional with emphasis on the geometry and overall combustion processes. 1D Plasma- Coal numerical experiments gave the predicted temperatures and velocities of gas and solids along the chamber length; while the concentrations of the gas components (CO, CO2, H2, CH4, C6H6, N2, H2O) were reported for the chamber exit. The degree of coal gasification showed that 54% of coal carbon was gasified within the plasma chamber. 3D numerical results for plasma jet spreading length were in good agreement with the measured data, while the temperature profiles within the plasma chamber were over predicted. The predictions of main species concentrations reveal that oxygen was completely consumed with the exit product stream consisting of combustible gases, un-burnt volatiles and char particles.